Land Inequality, an over the years trend:A District Level Analysis of Punjab Province, Pakistan - Hina Mushtaq*, Sumaira Kanwal*, Sobia Saeed*, Dr. Munir Ahmad**, (International Journal of Scientific Research and Management (IJSRM), 2015)
A Gini Coefficient has been implied to measure the inequality in distribution of land in 34 districtsof Punjab province, Pakistan. There are large regional inequalities in distribution of land. Based on the studyfurther policy options are proposed including: reducing the market imperfections; land reforms to re-distributethe land assets to landless farmers and the marginal farmers.